Asuhan Keperawatan Gerontik pada Ny. A dengan Penerapan Terapi Relaksasi Otot Progresif terhadap Penurunan Kadar Gula Darah pada Penderita Diabetes Melitus Tipe II di Wilayah Kerja Puskesmas Sei Langkai Kota Batam - Rahmadhea Dangrichi Noveola; Didi Yunaspi (Jurnal Kesehatan Amanah, 2026)
Type II Diabetes Mellitus is a chronic metabolic disorder commonly found in the elderly due to insulin resistance and impaired pancreatic hormone secretion. This condition leads to elevated blood glucose levels, physical weakness, and decreased daily activity performance, which ultimately reduces quality of life. Blood glucose control can be achieved not only through pharmacological therapy but also by applying non-pharmacological approaches such as progressive muscle relaxation therapy. This study aims to determine the effect of progressive muscle relaxation therapy on blood glucose levels in elderly patients with Type II Diabetes Mellitus. This research employed a case study method involving Mrs. A, an elderly patient experiencing hyperglycemia with a fasting blood glucose level of 247 mg/dl. The intervention was carried out over three consecutive days, consisting of progressive muscle relaxation exercises for 15–20 minutes per session, accompanied by dietary education, light physical exercise, and fall prevention guidance. Data were collected through observation, interviews, and blood glucose measurements before and after the intervention. The results showed a decrease in blood glucose level from 215 mg/dl to 158 mg/dl after three therapy sessions. The patient appeared more relaxed, experienced reduced fatigue, improved sleep quality, and demonstrated better urinary control. Conclusion: progressive muscle relaxation therapy is effective in lowering blood glucose levels and improving both physical and psychological conditions in elderly patients with Type II Diabetes Mellitus.